2023
DOI: 10.1111/ene.16057
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and prognosis of asymptomatic intracranial atherosclerosis in a community‐based population: Results based on high‐resolution magnetic resonance imaging

Shengde Li,
Mingyu Tang,
Dingding Zhang
et al.

Abstract: Background and purposeIntracranial atherosclerotic disease (ICAD) is a major cause of ischemic stroke in China, but the prevalence and prognosis of asymptomatic ICAD detected using high‐resolution magnetic resonance imaging (HR‐MRI) is largely unknown. The aim of this study was to investigate the prevalence and prognosis in order to guide neurologists in interpreting ICAD detected on HR‐MRI.MethodsWe included stroke‐free participants from a community‐based prospective cohort (Shunyi study participants) who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…The predictive accuracy of ML proves superior to that of conventional statistical approaches [ 8 , 9 ]. Previous studies indicate the linkage of patients with sICH prognosis to numerous elements, including demographic factors, hematoma volume, site of hemorrhage, inflammatory responses, and pharmaceutical impacts, cumulatively influencing the prognosis outcomes of sICH patients [ 10 13 ]. ML can analyze extensive data sets to uncover obscured predictive risk factors for enhanced clinical direction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predictive accuracy of ML proves superior to that of conventional statistical approaches [ 8 , 9 ]. Previous studies indicate the linkage of patients with sICH prognosis to numerous elements, including demographic factors, hematoma volume, site of hemorrhage, inflammatory responses, and pharmaceutical impacts, cumulatively influencing the prognosis outcomes of sICH patients [ 10 13 ]. ML can analyze extensive data sets to uncover obscured predictive risk factors for enhanced clinical direction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the prognosis value of HR‐MRI to predict recurrent stroke in acute stroke patients [3] [4], but the value of HR‐MRI in predicting first‐ever stroke is still unknown. In this Journal issue, the article by Li et al describes a community‐based prospective cohort study that included 1060 stroke‐free participants evaluated by HR‐MRI that found ICAD detected using HR‐MRI increases the long‐term risk of a first‐ever ischemic stroke by 2.5 times in a stroke‐free Chinese population, after adjusting for other risk factors [5]. This is the largest sample size study using HR‐MRI on ICAD with a long follow‐up duration of more than 4 years on average.…”
mentioning
confidence: 99%